Nomogram reliability for predicting potential risk in postgraduate medical students with anxiety symptoms. Issue 10 (October 2022) - Huang, Zewen; Zhang, Lejun; Wang, Junyu; Wang, Tingting; Xu, Lu; Yang, Xialing; Lu, Heli
Abstract: Purpose: This research aims to develop a Nomogram for exact anxiety symptoms prediction in postgraduate medical students so that they may be identified as high-risk individuals early and get focused care. Methods: Using a convenient sampling method, for case-control matching, 126 participants with anxiety symptoms and 774 participants of the same age and gender but without anxiety symptoms were designated as the case group and control group, respectively. Multivariable logistic regression analysis was utilized to identify influencing factors for anxiety symptoms, then used to design and verify a Nomogram of anxiety symptoms. Results: Multivariate logistic regression analysis showed that lack of social support (OR = 0.95, 95%CI: 0.91–0.99), low life satisfaction (OR = 0.91, 95%CI: 0.86–0.95), low subjective well-being (OR = 0.58, 95%CI: 0.41–0.83) and frequent tobacco and alcohol use (OR = 1.75, 95%CI: 1.10–2.80) were independent predictors of anxiety symptoms in postgraduate medical students ( P < 0.05). The Nomogram risk prediction model based on the above four independent prediction factors was established, and the verified C-index (Concordance index) is 0.787 (95%CI: 0.744–0.803, P < 0.001). Conclusions: Anxiety symptoms in postgraduate medical students are influenced by various variables. The Nomogram prediction model has high accuracy, validity, and reliability, which can provide reference for predicting anxiety symptoms in postgraduate medical students. Abstract : Anxiety symptoms; Medical students; Nomogram; Case-control study.